Use of herbal medicine to treat complaints during pregnancy - Neti Sulami; Dian Mariza RA; Susanti, Susanti (Jurnal EduHealth, 2024)
These complaints during pregnancy usually result in pregnant women self-medicating by using over-the-counter (OTC) medications, seeking prescribed medications, or using herbs. Herbal products are preferred over prescription drugs because it is believed that herbs are safer for the fetus than modern drugs. This research is a quantitative descriptive research. The purpose of this study was to identify the use of herbal medicine in pregnant women in dealing with complaints during pregnancy. This research was conducted in Bima City in September 2023 with a sample size of 34 pregnant women. The analysis used was univariate analysis by calculating the frequency distribution. The results of the study obtained were herbal ingredients that were often used to overcome during complaints consisted of turmeric temulawak kencur ginger cloves nutmeg guava leaves bidara bark garlic bangle Javanese chili, the type of preparation that was often used was consuming concoctions / decoctions and the use of shaken parems such as betel nut by 56% and the least use of concoctions / decoctions by 3%. Based on the indication of use, most pregnant women use herbal medicine to overcome nausea and vomiting and lack of appetite, each by 41%, and based on the desired effect, most pregnant women get a relaxing or calming effect by 94%.